CHATGPT UTILIZATION IN ACADEMIC PRACTICES: INSIGHTS FROM ENGLISH LANGUAGE EDUCATION STUDENTS IN THE DIGITAL ERA - Aziz, Abdul; Susanto, Herry Wahyudi; Irwandi, Febri; Trince, Merliana; Setiawan, Mariano; Widyawati, Widyawati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT The development of Artificial Intelligence (AI) presents new opportunities in higher education, including in the English Language Education Study Program. One prominent AI innovation is ChatGPT, a language model capable of generating text, answering questions, and providing feedback in various academic contexts. This study focuses on the use of ChatGPT in academic practice from the perspective of English Language Education students. The research method used a qualitative case study approach involving active students who have used ChatGPT regularly. Data were collected through in depth interviews, document observation, and field notes, then analyzed using NVivo assisted thematic analysis to identify patterns of perception, benefits, and challenges. The results show that students view ChatGPT as an effective tool for improving grammar, expanding vocabulary, organizing ideas, and increasing the efficiency of writing academic assignments. However, some students also acknowledged the risks of dependency, ethical dilemmas, and decreased creativity if used excessively. The study's conclusions emphasize the importance of ethical guidelines and digital literacy so that the use of ChatGPT not only improves academic skills but also strengthens students' critical thinking and originality. Perkembangan Kecerdasan Buatan Artificial Intelligence (AI) menghadirkan peluang baru dalam pendidikan tinggi, termasuk pada Program Studi Pendidikan Bahasa Inggris. Salah satu inovasi AI yang menonjol adalah ChatGPT, sebuah model bahasa yang mampu menghasilkan teks, menjawab pertanyaan, dan memberikan umpan balik dalam berbagai konteks akademik. Penelitian ini berfokus pada pemanfaatan ChatGPT dalam praktik akademik dari perspektif mahasiswa Pendidikan Bahasa Inggris. Metode penelitian menggunakan pendekatan studi kasus kualitatif yang melibatkan mahasiswa aktif yang secara rutin menggunakan ChatGPT. Data dikumpulkan melalui wawancara mendalam, observasi dokumen, dan catatan lapangan, kemudian dianalisis menggunakan analisis tematik berbantuan NVivo untuk mengidentifikasi pola persepsi, manfaat, dan tantangan. Hasil penelitian menunjukkan bahwa mahasiswa memandang ChatGPT sebagai alat yang efektif untuk meningkatkan kemampuan tata bahasa, memperluas kosakata, mengorganisir ide, serta meningkatkan efisiensi dalam menyelesaikan tugas akademik. Namun, beberapa mahasiswa juga mengakui adanya risiko ketergantungan, dilema etika, dan menurunnya kreativitas jika digunakan secara berlebihan. Kesimpulan penelitian menekankan pentingnya panduan etika dan literasi digital agar penggunaan ChatGPT tidak hanya meningkatkan keterampilan akademik, tetapi juga memperkuat kemampuan berpikir kritis dan orisinalitas mahasiswa.